Analisis Implementasi Fatwa DSN-MUI No. 4 Tahun 2000 dalam Perspektif Hukum Praktik Perbankan Syariah di Indonesia - Fauzi Ar Rozi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Fatwa DSN-MUI No. 4 of 2000 is a crucial guideline in Islamic banking practices in Indonesia, regulating the fundamental principles and operations of Islamic financial institutions. This study aims to analyze the implementation of the fatwa within the context of Islamic banking in Indonesia, focusing on the challenges encountered and potential solutions. The research methodology involves a qualitative approach with document analysis and interviews with Islamic banking practitioners. Findings reveal that while the fatwa provides clear guidelines, its implementation still faces several challenges, such as differing interpretations of Sharia principles and limited human resources. Proposed solutions include enhanced training for Islamic banking staff and the development of more effective supervision systems to ensure compliance with Sharia principles.